2020
DOI: 10.1515/ntrev-2020-0035
|View full text |Cite
|
Sign up to set email alerts
|

Tribological performance of nano-diamond composites-dispersed lubricants on commercial cylinder liner mating with CrN piston ring

Abstract: AbstractThis work investigated the effect of nanodiamond (ND) additives on the tribological properties of CrN-coated piston ring mating with the chromium-plated and BP alloy iron cylinder liners, which is one of the key friction pairs in the internal combustion engines. To enhance the dispersion of the NDs in the base oil, the surface of ND particles was modified with polyaniline via in situ polymerization. The friction and wear as well as the scuffin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 47 publications
(47 reference statements)
0
6
0
Order By: Relevance
“…At loads higher than those used in the present work, Al alloy would experience severe wear, and at much higher loads it would fail catastrophically by scuffing [30]. ND particles would prove beneficial at higher loads in terms of lowering wear, as they have anti-scuffing ability [3].…”
Section: Wear Behaviormentioning
confidence: 74%
See 1 more Smart Citation
“…At loads higher than those used in the present work, Al alloy would experience severe wear, and at much higher loads it would fail catastrophically by scuffing [30]. ND particles would prove beneficial at higher loads in terms of lowering wear, as they have anti-scuffing ability [3].…”
Section: Wear Behaviormentioning
confidence: 74%
“…A report by Mochalin et al [2] gives a detailed account of the properties and applications of nanodiamonds. Recent work on commercial Cr cylinder liner/CrN-coated piston ring tests has identified the anti-scuffing ability of ND particles [3]. Diesel engine tests have shown that ND particles as engine oil additives increase maximum engine power and maximum torque, reduce entire engine's mechanical loss, and enhance heat transfer and fuel efficiency [4].…”
Section: Introductionmentioning
confidence: 99%
“…This indicates that the lubricant film between the two sliding surfaces was in the mixed lubrication or hydrodynamic lubrication region that creates a wedge and clearance between the surfaces in motion which reduced the coefficient of friction. Study done by Huang et al, [13] shows that coefficient of friction decreased as the normal load increased when tested the CrN coated piston ring with nano-diamond additive lubricants.…”
Section: Coefficient Of Frictionmentioning
confidence: 94%
“…Therefore, the friction reduction achieved through employing engine lubricating oils keeps and attracts intensive attention as an effective way to improve engine efficiency [ 69 , 75 ]. Huang et al [ 76 ] investigated the effect of NCD powders in lubricating oil on the tribological performances between CrN-coated piston rings and chromium-plated and BP-alloyed iron cylinder liners by using the reciprocating sliding tribometer, which is one of the key friction pairs in the internal combustion engine.…”
Section: Ncd For Tribological Applicationsmentioning
confidence: 99%